Pressure–temperature–deformation–time path of a deformed garnet-bearing granite from the Paleoproterozoic Tandilia Belt, Río de la Plata Craton of Argentina - Angeletti, Melisa (2021)
The pressure–temperature (P–T) evolution of a deformed garnet-bearing granite of La Virgen hill, located 25 km south of the town of Azul, Argentina, was studied as an example of the slightly peraluminous and deformed granites widespread in the Paleoproterozoic Tandilia Belt of the Rio de la Plata Craton. An early isobaric magmatic–submagmatic cooling path followed by exhumation was derived by the appraisal of microstructures, chemical compositions of minerals and P–T pseudosection modeling in the system Si–Ti–Al–Fe–Mn–Mg–Ca–Na–K–O–H (1 wt.% of H2O) using the software PERPLE_X. Slightly zoned magmatic garnet with a core composition of pyr4(grs + adr)11sps10alm75 equilibrated with plagioclase (XAn = 0.37) at 6.0 kbar and 655 °C in a crystal mush with < 7 vol.% of melt. The garnet rim composition of pyr3(grs + adr)12sps14alm71, texturally equilibrated with biotite (Mg/(Mg + Fe) = 0.21) at the granitic solidus of 5.9 kbar and 645 °C. The subsequent cooling path is constrained by isopleths of low-Ti muscovite with Si contents of 3.17 per formula unit commonly located around K-feldspar and recrystallized plagioclase (XAn = 0.35). Ductile deformation at low amphibolite- to greenschist-facies metamorphic conditions produced the subvertical main foliation. Forty-two chemical analyses in seven monazite grains of the granite yielded two groups of U–Th–Pb ages at 2126 ± 10 (2σ) Ma and 2089 ± 3 Ma, interpreted to be inherited from widespread magmatic events of the Tandilia Belt and resulted from the granite crystallization, respectively. The exhumation of the deformed granite from middle (~ 22 km) to upper and cold crustal levels was probably a long-lasting process after 1.9 Ga.